Magnetic nanoribbons with embedded cobalt grown inside single-walled carbon nanotubes. Issue 5 (21st January 2022) - Krichevsky, Denis M.; Shi, Lei; Baturin, Vladimir S.; Rybkovsky, Dmitry V.; Wu, Yangliu; Fedotov, Pavel V.; Obraztsova, Elena D.; Kapralov, Pavel O.; Shilina, Polina V.; Fung, Kayleigh; Stoppiello, Craig T.; Belotelov, Vladimir I.; et al.
Abstract : Magnetic nanoribbons were grown inside single-walled carbon nanotubes. The fingerprint features of CoPc nanoribbons we identified and confirmed the encapsulation. An impact of magnetic Co atoms was verified using TMOKE measurements. Abstract : Molecular magnetism and specifically magnetic molecules have recently gained plenty of attention as key elements for quantum technologies, information processing, and spintronics. Transition to the nanoscale and implementation of ordered structures with defined parameters is crucial for advanced applications. Single-walled carbon nanotubes (SWCNTs) provide natural one-dimensional confinement that can be implemented for encapsulation, nanosynthesis, and polymerization of molecules into nanoribbons. Recently, the formation of atomically precise graphene nanoribbons inside SWCNTs has been reported. However, there have been only a limited amount of approaches to form ordered magnetic structures inside the nanotube channels and the creation of magnetic nanoribbons is still lacking. In this work we synthesize and reveal the properties of cobalt-phthalocyanine based nanoribbons (CoPcNRs) encapsulated in SWCNTs. Raman spectroscopy, transmission electron microscopy, absorption spectroscopy, and density functional theory calculations allowed us to confirm the encapsulation and to reveal the specific fingerprints of CoPcNRs. The magnetic properties were studied by transverse magnetooptical Kerr effect measurements, which indicated a strong difference in comparison with the pristine unfilled SWCNTs due to the impact of Co incorporated atoms. We anticipate that this approach of polymerization of encapsulated magnetic molecules inside SWCNTs will result in a diverse class of protected low-dimensional ordered magnetic materials for various applications.